Efficacy of surface landmark palpation for identification of the cricoid cartilage in obstetric patients: A prospective observational study - Fatemah Qasem; Roy Khalaf; Ilana Sebbag; Ronit Lavi; Philip M Jones; Sudhu Indu Singh (Wolters Kluwer Medknow Publications, 2019)
Background and Aims: Rapid sequence induction, with the application of cricoid pressure is an accepted practice during induction of general anesthesia in pregnant patients to prevent pulmonary apiration. We found no prior studies assessing the accuracy of locating the cricoid cartilage by professional caregivers, and therefore conducted an observational study to assess the ability of different caregivers - anesthesia consultants, anesthesia residents, respiratory therapists (RTs), and nurses, in the obstetric care unit, to correctly identify the cricoid cartilage of parturients. We hypothesized that anesthesia consultants would be most accurate. Material and Methods: Institutional REB approval was obtained, as was written informed consent from all participants in the study. The subjects were made up of thirty healthy obstetric patients scheduled for elective cesarean delivery. Their cricoid cartilages were assessed by 53 caregivers (assessors). Localization of the cricoid cartilage by assessors was considered accurate if it was within 5 mm of the sonographically identified mark. The difficulty in localization was reported on a VAS scale and the time taken for localization was recorded. Results: Data from 30 subjects and 53 assessors (13 anesthesia consultants, 12 residents, 13 RTs, and 15 nurses) performing a total of 60 evaluations (some assessors evaluated 2 subjects) were analyzed. About 60% of RTs, 53% of anesthesia residents, 40% of anesthesia consultants, and 13% of nurses correctly identified the cricoid cartilage. No differences in caregivers'perception of difficulty were found, but RTs were the quickest at identification (P < 0.001 vs anesthesia consultants; P = 0.002 vs residents; P = 0.071 vs nurses). Conclusion: RTs were the most successful and accurate in identifying the cricoid cartilage of parturients among the different groups of professional caregivers.